Collagen has a unique SEC24 preference for efficient export from the endoplasmic reticulum. (22nd November 2021) - Lu, Chung‐Ling; Ortmeier, Steven; Brudvig, Jon; Moretti, Tamara; Cain, Jacob; Boyadjiev, Simeon A.; Weimer, Jill M.; Kim, Jinoh
Abstract: SEC24 is mainly involved in cargo sorting during COPII vesicle assembly. There are four SEC24 paralogs (A–D) in vertebrates, which are classified into two subgroups (SEC24A/B and SEC24C/D). Pathological mutations in SEC24D cause osteogenesis imperfecta with craniofacial dysplasia in humans. sec24d mutant fish also recapitulate the phenotypes. Consistent with the skeletal phenotypes, the secretion of collagen was severely defective in mutant fish, emphasizing the importance of SEC24D in collagen secretion. However, SEC24D patient‐derived fibroblasts show only a mild secretion phenotype, suggesting tissue‐specificity in the secretion process. Using Sec24d KO mice and cultured cells, we show that SEC24A and SEC24B also contribute to endoplasmic reticulum (ER) export of procollagen. In contrast, fibronectin 1 requires either SEC24C or SEC24D for ER export. On the basis of our results, we propose that procollagen interacts with multiple SEC24 paralogs for efficient export from the ER, and that this is the basis for tissue‐specific phenotypes resulting from SEC24 paralog deficiency. Abstract : SEC24D gene mutations cause predominantly bone defects. A prevailing explanation is that SEC24D sorts procollagen. Using Sec24d KO mice and cultured cells, we show that SEC24A and SEC24B also contribute to endoplasmic reticulum (ER) export of procollagen. In contrast, fibronectin 1 requires either SEC24C or SEC24D for ER export. This finding is significant as it forms the basis for tissue‐specific and cargo‐specific utilization of SEC24 paralogs for ER export.